Perkembangan Teknologi Informasi dan Komunikasi dalam Upaya Menanggulangi Plagiarisme Dikalangan Mahasiswa - Aditya Pratama (Universitas Indraprasta PGRI Jakarta, 2018)
The development of ICT offers an improvement in the quality of education. The use of ICT greatly contributes to the improvement in the quality of education. ICT provides various facilities in obtaining information. The easiness of obtaining information can improve the quality of the learning process. However, behind the benefits derived from the use of ICT, there is concern about plagiarism. Plagiarism is strictly prohibited in the world of education. The sanctions imposed for the action is even set in the Law. The Formulation of Problems: How is the development of ICT in education?, How is the view of plagiarism among students? The research objective is to analyze the development of ICT in education. This research uses a qualitative research method comprising of the data collection, data reduction, data presentation and conclusion. The results of the analysis indicate that 43.24% of respondents intentionally commit plagiarism. Most of informants in the research state that the respondents know that the students commit plagiarism. The use of the Garuda portal and turnitin.com portal may prevent the plagiarism among students from happening